That "vision thing": Formulating a winning policy agenda - Pavlina R. Tcherneva; L. Randall Wray (Levy Economics Institute of Bard College, 2025)
In recent elections, Republicans and Democrats have been competing for the votes of the suburban middle class. The pocketbook issues of the working class have been largely ignored by both parties-this group comprises the true swing voters (voting for Trump in 2016 and 2024 and for Biden in 2020), but their votes are largely protest votes, against incumbents who have not delivered for them. In this policy brief, Institute President Pavlina R. Tcherneva and Senior Scholar L. Randall Wray examine the shifting allegiances of American voters and the types of policies they favor. Tcherneva and Wray are primarily interested in the types of economic policies that would improve the well-being of American working class families and outline some of the economic policies that could win this group over for the next election. As the authors note, while not every "popular" policy is a good policy, good progressive policies are far more popular with the electorate than is typically recognized by either party.
Keywords: 330; Job guarantee; Policy space; Political economy; Well-being